Applying the Toyota production system to decrease the time required to transport patients undergoing surgery from the general ward to the operating room and reviewing the essence of lean thinking - Lin, Chien-Chung; Chueh, Jui-Wen; Chen, Hung-Ming; Chiu, Yao-Hui; Chu, Dachen (Frontiers in Medicine, 2022)
Background: Sending a patient to the operating room is the first step in surgery. Delayed patient transport causes the patient to go hungry for a longer time, aggravating the patient’s physical discomfort and psychological stress. The issue of delays in transporting inpatients to the operating room has rarely been discussed in the literature. The Toyota production system is a famous and excellent scientific method of reducing waste and increasing efficiency. Our goal is to use the Toyota method to decrease the time required to transport the inpatient to the operating room and to review the concepts underlying lean thinking. Methods: We employed an A3 8-step problem-solving process. A current value stream map featuring numerical data (concerning 46 patients) measured in the workplace was developed. The total time spent on transport was 53 minutes, but we expected patients to be transported within 30 minutes. We hoped to reduce the time wasted by half, i.e., by 23*50%=12 minutes. These 12 minutes were saved by reducing the time spent on "waiting for an attendant at the ward" by 9 minutes and the time spent on "elevator transport" by 3 minutes. According to the value stream map featuring the time measurements, the root causes of delayed transportation can be divided into process-related, attendant-related, and elevator-related factors. We formulated 5 countermeasures. The ECRS (Eliminate, Combine, Rearrange, Simplify) technique was used to rearrange, combine, and simplify the existing process. Hospital executives established norms for attendant prioritization of work and rules for elevator use. Results: According to the original indicators, all goals were attained. "Total time spent" decreased by 62.3%. The time required for attendants to report to the nursing station decreased by 56.5%. The time spent on elevator transport decreased by 44.4%. We developed a process for future use based on information-assisted patient and staff identification. Finally, we standardized successful processes. Conclusions: The seemingly trivial factors that delay patient transport are associated with seven types of waste. The A3 8-step problem-solving process is useful in this context. In proposing this improvement process, we believe that we are following the spirit of the Toyota production system.